VENOUS ACCESS INDICATION ALGORITHM FOR NEWBORNS IN NEONATAL INTENSIVE CARE UNIT - Giacomozzi, Clélia Mozara; Giacomozzi, Letícia Morgana; Silva, Regina Paula Vieira Cavalcante da; Mittag, Bárbara Franco; Nunes, Regina Célia Tanaka (Cogitare Enfermagem, 2023)
Objective: to present an algorithm for the indication of venous accesses for newborns in Neonatal Intensive Care Unit. Development: descriptive study conducted in a Neonatal Intensive Care Unit in southern Brazil, in the period from 2017 to 2020 in two stages of idealization: design of the algorithm; and the adequacy based on the application according to observations made by the nurses involved. The developed algorithm contemplated the prediction of venous access for patients with indication for abdominal and other surgeries, premature infants stratified in gestational age higher and lower than 30 weeks, heart diseases with dependence or not on arterial channel and persistent neonatal hypoglycemia. According to the venous network, number of prescribed therapies, fasting, antibiotic therapy and vasoactive drugs, there is an initial indication for one type of catheter that may be followed by another according to need. Conclusion: the participation of nurses in the indication of venous access integrates interprofessional practices and increases neonatal care.